2013
DOI: 10.1158/1078-0432.ccr-12-0930
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Adiponectin and Leptin Signaling in Cancer

Abstract: The increasing percentage of obese individuals in the population and its independent association of increased risk for the development of cancer have heightened the necessity to understand the molecular mechanisms that underlie this connection. The deregulation of adipokines in the setting of obesity and their impact on cancer progression and metastasis is one such area of research. Adipokines are bioactive proteins that mediate metabolism, inflammation, angiogenesis, and proliferation. Altered levels of adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(179 citation statements)
references
References 98 publications
(99 reference statements)
2
171
1
5
Order By: Relevance
“…These molecules will then regulate several pathways of pivotal importance to cancers, such as the AKT/mTOR/PI3K and ERK/MAPK pathways, involved in cell growth and survival; COX2, IL1, and NFkB, related to inflammation; and VEGFs, involved in angiogenesis (Surmacz 2013). Thus, leptin interacts with several factors that participate in diverse carcinogenic stages, and its relationship with breast, prostate, colorectal, hepatocellular, pancreatic, and lung cancers, as well as thyroid cancer, has consistently been demonstrated in the literature (Dutta et al 2012, Vansaun 2013. Concerning thyroid cancers, and more specifically DTCs, leptin and OBR (LEPR) expression were first demonstrated by Cheng et al (2010b), who found them associated with a high risk of lymph node metastases.…”
Section: Inflammationmentioning
confidence: 96%
“…These molecules will then regulate several pathways of pivotal importance to cancers, such as the AKT/mTOR/PI3K and ERK/MAPK pathways, involved in cell growth and survival; COX2, IL1, and NFkB, related to inflammation; and VEGFs, involved in angiogenesis (Surmacz 2013). Thus, leptin interacts with several factors that participate in diverse carcinogenic stages, and its relationship with breast, prostate, colorectal, hepatocellular, pancreatic, and lung cancers, as well as thyroid cancer, has consistently been demonstrated in the literature (Dutta et al 2012, Vansaun 2013. Concerning thyroid cancers, and more specifically DTCs, leptin and OBR (LEPR) expression were first demonstrated by Cheng et al (2010b), who found them associated with a high risk of lymph node metastases.…”
Section: Inflammationmentioning
confidence: 96%
“…LEP signals are pro-angiogenic, pro-inflammatory, and mitogenic and are mediated via multiple cross-regulatory pathways involving oncogenes, cytokines, and growth factors, driving growth of solid tumors (19,20). LEP activates JAK2/STAT3, MAPK/ERK1/2, and PI3K/AKT signaling pathways (2,21).…”
Section: Leptin (Lep)mentioning
confidence: 99%
“…Breast cancer is one of the most common malignancies in women worldwide, with multiple risk factors identified, including differential expression of adipocytokines (1,2). Visfatin, also known as nicotinamide phosphoribosyltransferase (NAMPT) or pre-B-cell colony-enhancing factor (PBEF), is a 52 kDa adipocytokine discovered both intracellularly and extracellularly (3).…”
Section: Introductionmentioning
confidence: 99%